1992
DOI: 10.1177/07399863920142004
|View full text |Cite
|
Sign up to set email alerts
|

A Note on the Relationship between Acculturation and Socioeconomic Status

Abstract: Studies investigating the acculturation of Hispanic-Americans often overlook socioeconomic status (SES) as an important correlate with acculturation. This study examined the relationship between acculturation and SES among a group of Mexican-American college students. A significant positive relationship was found between acculturation and SES even when SES was inferred via different indicators. The importance of accounting for SES when examining acculturation is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 12 publications
1
37
0
Order By: Relevance
“…(41) Many of the risk factors for asthma that are found in poorer households in general may actually be less common among poorer, less acculturated, Hispanic households. (42) Increased acculturation has been linked to higher prevalence of asthma risk factors including shorter duration of breastfeeding,(43) smoking,(44) prematurity(45, 46) and poor diet,(47) and has been shown to be a risk factor for asthma among Mexican Hispanics. (48, 49) Although we adjusted for the subject child’s birth outside the U.S., our analyses did not adjust for the immigration status of the child’s parent, and thus acculturation is a potential explanation for the inverse relationship between poverty and asthma we found among Hispanics, although differences in diagnosis and gene-by-environment interactions may also play a role.…”
Section: Discussionmentioning
confidence: 99%
“…(41) Many of the risk factors for asthma that are found in poorer households in general may actually be less common among poorer, less acculturated, Hispanic households. (42) Increased acculturation has been linked to higher prevalence of asthma risk factors including shorter duration of breastfeeding,(43) smoking,(44) prematurity(45, 46) and poor diet,(47) and has been shown to be a risk factor for asthma among Mexican Hispanics. (48, 49) Although we adjusted for the subject child’s birth outside the U.S., our analyses did not adjust for the immigration status of the child’s parent, and thus acculturation is a potential explanation for the inverse relationship between poverty and asthma we found among Hispanics, although differences in diagnosis and gene-by-environment interactions may also play a role.…”
Section: Discussionmentioning
confidence: 99%
“…Although other studies have shown that increasing acculturation and education each are associated with increased leisure-time physical activity [7,3638], and indeed some studies have suggested the role of interaction shaping Latino health more generally [39,40], little empirical evidence exists documenting the extent to which education modifies associations between acculturation and physical activity (or vice versa). The joint effects we observed may be attributable to fundamental resources [21], where individuals with greater SEP and greater English-language use may be able to avail themselves of the benefits of being physically active.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, marginalizaed individuals neither maintain their own culture nor connect with the dominant culture. The development and deployment of specific acculturative strategies are influenced by personal attributes such as age, socioeconomic status (SES), and language acquisition (Dow 2011), which determine the variation in the degree and rate of acculturation across groups and across individuals of the same group (Berry 1997;Dow 2011;Negy and Woods 1992). Immigrants with higher level of SES have more social, intellectual, and economic resources to overcome the external barriers (i.e., better acculturative strategies) and to cope with their internal distress (Dow 2011).…”
Section: Culture Acculturation and Intimate Partner Violence Among mentioning
confidence: 99%